Dying for a meal all about food poisoning - Stone, Martin; Barrett, Neil; Video Education Australasia (Bendigo, Vic.: Video Education Australasia, 1998)
This program introduces us to the different forms of bacteria which cause food poisoning
Keywords: Food handling; Food service -- Sanitation; Food Contamination -- prevention & control; Food poisoning